Liquid Biopsy for Invasive Mold Infections in Hematopoietic Cell Transplant Recipients With Pneumonia Through Next-Generation Sequencing of Microbial Cell-Free DNA in Plasma. (29th October 2020) - Hill, Joshua A; Dalai, Sudeb C; Hong, David K; Ahmed, Asim A; Ho, Carine; Hollemon, Desiree; Blair, Lily; Maalouf, Joyce; Keane-Candib, Jacob; Stevens-Ayers, Terry; Boeckh, Michael; Blauwkamp, Timothy A; et al.
Abstract: Background: Noninvasive diagnostic options are limited for invasive mold infections (IMIs). We evaluated the performance of a plasma microbial cell-free DNA sequencing (mcfDNA-Seq) test for diagnosing pulmonary IMI after hematopoietic cell transplant (HCT). Methods: We retrospectively assessed the diagnostic performance of plasma mcfDNA-Seq next-generation sequencing in 114 HCT recipients with pneumonia after HCT who had stored plasma obtained within 14 days of diagnosis of proven/probable Aspergillus IMI (n = 51), proven/probable non- Aspergillus IMI (n = 24), possible IMI (n = 20), and non-IMI controls (n = 19). Sequences were aligned to a database including >400 fungi. Organisms above a fixed significance threshold were reported. Results: Among 75 patients with proven/probable pulmonary IMI, mcfDNA-Seq detected ≥1 pathogenic mold in 38 patients (sensitivity, 51% [95% confidence interval CI, 39%–62%]). When restricted to samples obtained within 3 days of diagnosis, sensitivity increased to 61%. McfDNA-Seq had higher sensitivity for proven/probable non- Aspergillus IMI (sensitivity, 79% [95% CI, 56%–93%]) compared with Aspergillus IMI (sensitivity, 31% [95% CI, 19%–46%]). McfDNA-Seq also identified non- Aspergillus molds in an additional 7 patients in the Aspergillus subgroup and Aspergillus in 1 patient with possible IMI. Among 19 non-IMI pneumonia controls, mcfDNA-Seq was negative in all samples, suggesting a high specificity (95% CI, 82%–100%) and up to 100% positive predictive value (PPV) with estimated negative predictive values (NPVs) of 81%–99%. The mcfDNA-Seq assay was complementary to serum galactomannan index testing; in combination, they were positive in 84% of individuals with proven/probable pulmonary IMI. Conclusions: Noninvasive mcfDNA-Seq had moderate sensitivity and high specificity, NPV, and PPV for pulmonary IMI after HCT, particularly for non- Aspergillus species. Abstract : In this retrospective study of 114 hematopoietic cell transplant recipients with pneumonia, microbial cell-free DNA sequencing (mcfDNA-Seq) had moderate sensitivity and high specificity for detecting pathogenic molds in plasma, particularly for non- Aspergillus species. McfDNA-Seq may be a useful test to reduce invasive procedures and guide treatment.